Analysis of powdered calendula officinalis linn: A study on the analysis of powdered Calendula officinalis Linn using thin-layer chromatographic technique (Journal of Advances and Scholarly Researches in Allied Education, 2022)
India is well recognized as an ancient culture with a rich tradition of herbal medicine. The vastmajority of the raw materials used in the pharmaceutical and perfume industries come from India's forests,where a plethora of fragrant and therapeutic plants are gathered. Calendula officinalis is a member of thedaisy family (Asteraceae) that is native to southern Europe or the Eastern Mediterranean. It may begrown as an annual or short-lived perennial. It's been a garden staple for decades, and now it's poppingup all over the place in milder temperatures by itself. In this research, a high-performance thin-layerchromatographic technique was modified to be sensitive, straightforward, and accurate in its analysis ofpowdered Calendula officinalis Linn.